การสื่อสารของคณะละครหุ่นร่วมสมัยในประเทศไทย - วณิชชา ภราดรสุธรรม (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
To study the evolution of Thai contemporary puppet companies and also patterns and contents of contemporary puppet’s presentation. Mixed methods applied to the study were ; conducting an audience opinion survey via questionnaires, conducting in-depth interviews with 7 experts, gathering and analyzing contents of Thai contemporary puppet . The study shows that the evolution of Thai contemporary puppet takes part as a plays for children and resulting a contemporary puppet’s community that leads to a Thai culture representation. There are 2 different forms of Thai contemporary puppet. First, is the influence of puppet’s creation and second, is the method of puppet’s manipulation. Contents of contemporary puppet presentation separates into 2 cases. First is in case of new contents writing and second is the contents recreation. The result of general audience’s attitude towards Thai contemporary puppet shows that most of them are rarely watch contemporary puppet (60.50 percent) and the factor that represents Thai culture is the puppet. (27.63%). The satisfaction of general audience separates into 3 parts. First, is the satisfaction of contents. Second, is the satisfaction of factors of Thai contemporary puppet and third, is the satisfaction of social’s avail. However, audiences are very satisfy on the average.